2013
DOI: 10.1182/blood-2013-02-485524
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric acute myeloid leukemia with t(8;16)(p11;p13), a distinct clinical and biological entity: a collaborative study by the International-Berlin-Frankfurt-Münster AML-study group

Abstract: Key Points• Pediatric t(8;16)(p11;p13) AML is a rare entity defined by a unique gene expression signature and distinct clinical features.• Spontaneous remissions occur in a subset of neonatal t(8;16)(p11;p13) AML cases.In pediatric acute myeloid leukemia (AML), cytogenetic abnormalities are strong indicators of prognosis. Some recurrent cytogenetic abnormalities, such as t(8;16)(p11;p13), are so rare that collaborative studies are required to define their prognostic impact. We collected the clinical characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
116
3
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(127 citation statements)
references
References 49 publications
2
116
3
6
Order By: Relevance
“…AML with t(8;16)(p11;p13) has a very unique clinical/pathological picture and a poor prognosis, which has resulted in several proposals for a specific subclassification within the FAB system for this entity. As described above, the striking erythrophagocytosis displayed by blasts in AML with t(8;16)(p11;p13) has been discussed as a distinctive feature numerous times in the literature [2][3][4][5][6][7]9,10,14]. The breakpoint observed in AML with t(8;16) (p11;p13) involves genes that are central to erythropoiesis.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…AML with t(8;16)(p11;p13) has a very unique clinical/pathological picture and a poor prognosis, which has resulted in several proposals for a specific subclassification within the FAB system for this entity. As described above, the striking erythrophagocytosis displayed by blasts in AML with t(8;16)(p11;p13) has been discussed as a distinctive feature numerous times in the literature [2][3][4][5][6][7]9,10,14]. The breakpoint observed in AML with t(8;16) (p11;p13) involves genes that are central to erythropoiesis.…”
Section: Discussionmentioning
confidence: 93%
“…In the case series by Diab et al of 13 patients with AML with t(8;16)(p11;p13), 7 had blasts which exhibited erythrophagocytosis [2]. Amongst pediatric AML with t(8;16) (p11;p13), as many as 70% of cases reported show erythrophagocytosis [3]. Erythrophagocytosis is a relatively rare finding in other types of AML, so this characteristic should raise concern for t(8;16)(p11;p13) as the culprit mutation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three remain in complete remission during follow-up (ranging from 0.9 to 5 y), whereas 4 patients suffered disease recurrence. 7 Diab et al 8 also reported that an infant (age 2 mo) with t(8;16)(p11;p13) AML had spontaneous regression. These reports showed that some cases of t(8;16)(p11;p13) AML regress spontaneously.…”
Section: Discussionmentioning
confidence: 96%